Analysis Efficiency of BUMN Sharia Banks After the Merger - Nadiatul Hanifah; Deky Aji Suseno (Universitas Negeri Semarang, 2022)
The purpose of this study is to analyze the efficiency level of BUMN Islamic banking after the merger, analyze the value of input slack and output slack technical efficiency of BUMN Islamic banking after the merger in order to know which input or output causes inefficiency, and analyze the calculation of the ideal input and output values for efficiency. in state-owned Islamic banking after the merger. The data analysis technique in this research is Data Envelopment Analysis (DEA). Bank Syariah Indonesia after the merger at the beginning of its formation was declared inefficient in the period of February 2021 and April 2021. This is because there are obstacles in its input and output. Based on the results of the analysis that has been carried out, it can be seen that the average Technical Efficiency (TE) is 0.988 indicates that the maximum output that can be generated by BSI using available inputs and technology is around 98.8% of the potential of Bank Syariah Indonesia.